Impact of the 2015 wildfires on Malaysian air quality and exposure: a comparative study of observed and modeled data - Mead, Mohammed Iqbal; Castruccio, S.; Latif, M. T.; Nadzir, Mohd Shahrul Mohd; Dominick, D.; Thota, A.; Crippa, P. (Institute of Physics (IOP), 2018)
In September and October 2015, Equatorial Asia experienced the most intense biomass burning episodes over the past two decades. These events, mostly enhanced by the extremely dry weather associated with the occurrence of strong El Niño conditions, resulted in the transnational transport of hazardous pollutants from the originating sources in Indonesian Borneo and Sumatra to the highly populated Malaysian Peninsula. Quantifying the population exposure form this event is a major challenge, and only two model-based studies have been performed to date, with limited evaluation against measurements. This manuscript presents a new data set of 49 monitoring stations across Peninsular Malaysia and Malaysian Borneo active during the 2015 haze event, and performs the first comparative study of PM10 (particulate matter with diameter < 10 µm) and carbon monoxide (CO) against the output of a state-of-the-art regional model (WRF-Chem). WRF-Chem presents high skills in describing the spatio-temporal patterns of both PM10 and CO and thus was applied to estimate the impact of the 2015 wildfires on population exposure. This study showed that more than 60% of the population living in the highly populated region of the Greater Klang Valley was systematically exposed to unhealthy/hazardous air quality conditions associated with the increased pollutant concentrations from wildfires and that almost 40% of the Malaysian population was on average exposed to PM10 concentrations higher than 100 µg m−3 during September and October 2015.
Keywords: air quality; transnational pollution; particulate matter; wildfires; population exposure; equatorial Asia